Direct writing electrodes using a ball pen for paper-based point-of-care testing1. Issue 16 (21st August 2015) - Li, Zedong; Li, Fei; Hu, Jie; Wee, Wei Hong; Han, Yu Long; Pingguan-Murphy, Belinda; Lu, Tian Jian; Xu, Feng
<x xml:space="preserve">Abstract</x> A simple strategy to fabricate paper-based electrochemical devices has been developed by directly writing using a pressure-assisted ball pen.